Maize seed demand, supply and varietal age dynamics in Ethiopia - Kebede, Jeleta; Mohammed, Abdu; Jaleta, Moti (CIMMYT, 2025)
Despite a continuous maize varietal development in Ethiopia, farmers are using relatively old varieties. Against this backdrop, using the quantity of maize seed supply and distribution for the period of 2009-2023, this study analyses dynamics in maize varietal age in the country. Result shows that while average varietal age (AVA) of maize seed demanded, supplied, and distributed in the country gradually decreased overtime for both public and privately sourced hybrids, it was increasing for improved open-pollinated varieties (OPVs). We find that varietal age below threshold increases demand, supply and distribution of maize seed varieties, but varietal age above threshold reduces demand, supply and distribution of the varieties. We observe similar results for the effects of seed specific varietal age on demand, supply and distribution of the varieties. We further demonstrate that while there is a bidirectional causality between maize seed supply and distribution, the relationships between maize seed demand and supply, and demand and distribution are unidirectional: previous year supply and distribution cause demand for specific variety, but supply and distribution are not responding to previous demand. This implies that farmers’ varietal knowledge is limited to the varieties supplied to them in the previous season, and supply is driving demand. The results further imply that maize seed production and marketing focused on more recently released varieties in general and that of OPV in particular can be used as an instrument to reduce AVA thereby increasing varietal turnover.